Bottom‐Up On‐Surface Synthesis of Two‐Dimensional Graphene Nanoribbon Networks and Their Thermoelectric Properties. Issue 23 (28th November 2019) - Kojima, Takahiro; Nakae, Takahiro; Xu, Zhen; Saravanan, Chinnusamy; Watanabe, Kentaro; Nakamura, Yoshiaki; Sakaguchi, Hiroshi
Abstract: Graphene, the one‐atom‐thick two‐dimensional (2D) carbon material, has attracted tremendous interest in both academia and industry due to its outstanding electrical, mechanical, and thermal properties. For electronic applications, the challenging task is to make it as a semiconductor. The bottom‐up synthesis of semiconducting one‐dimensional (1D) nanometer‐wide graphene strips, namely, graphene nanoribbons (GNRs), has attracted much attention owing to its promising electronic, optical, and magnetic properties. In this regard, we report the fabrication of cove‐type 2D GNR networks (GNNs) via the interconnection of 1D self‐assembled GNRs on the surface of Au(111). The cove‐type 2D GNRs networks (GNNs) were fabricated from the GNR, 5‐CGNR‐1‐1, synthesized using the precursor of DBSP . Annealing of high‐density self‐assembled GNRs on the surface of Au(111) through two‐zone chemical vapour deposition (2Z CVD) successfully generated a 2D interconnected structure with high yield via the fusion and ladder coupling reactions of GNR chains. In order to validate the later fusion reaction, we have also synthesized the GNR, 7‐AGNR‐1‐1, using the precursor of DBBA . The GNNs, which consist of hybridized metallic‐like and semiconducting GNRs, are a new class of carbon‐based materials. Further, we applied this material for thermoelectric (TE) applications and found a very low cross‐plane thermal conductivity of 0.11 Wm −1  K −1, which is one of the lowest value among the carbon‐based materials as well as inorganic semiconductors, while maintaining the cross‐plane electrical conductivity of 188 S m −1 . Abstract : Two‐dimensional graphene nanoribbon networks (2D‐GNNs) : The fabrication of cove‐type 2D‐GNNs via the interconnection of one‐dimensional self‐assembled GNRs on the surface of Au(111) is reported along with thermoelectric (TE) applications. The material shows an ultralow cross‐plane thermal conductivity of 0.11 Wm −1  K −1, which is the lowest value among carbon‐based materials.